Problem solving in business and management : hard, soft and creative approaches - Hicks, Michael J. (London : Chapman and Hall, 1991)
Problems. Resolving problems. Decisions. Where has all our creativity gone? Working in groups. Brainstorming. Synectics. Introduction to logical thinking...
Keywords: Business management; Decision making